Public policies in groundwater management and their impact on rural development. - Ordóñez, Marjorie; América Herrerra, Gricelda; Luy Navarrete, Wayky; Merino Velásquez, Jesús (Revista Universidad de Guayaquil, 2019)
This article aims to analyze the importance of public policies for rural development and the role of the government administration on duty to guarantee that human rights are fulfilled, one of the vital rights being access to clean water and treatment of solid waste, in the social and economic development of a parish with unique characteristics within the environmental context. This study is qualitative, with descriptive characteristics, it is documentary with a review of the most relevant authors on the subject, relating the common aspects that each of them considers basic in the analysis of public policies. The result of the investigation reveals that the social and economic development of a rural parish is closely linked to the fulfillment of public policies consistent with the vision of a state, making them have the participation of the community, as well as government sectional agencies and the private action of international organizations dedicated to providing technical advice.
Keywords: Public politics; rural development; community participation